Comparative Performance Evaluation of TCP Variants in WiMAX (and WLANs) Network Configurations - Konstantinos Tsiknas; George Stamatelos (Journal of Computer Networks and Communications)
An important application for the IEEE 802.16 technology (also called WiMAX) is to provide high-speed access to the Internet where the transmission control protocol (TCP) is the core transport protocol. In this paper we study through extensive simulation scenarios the performance characteristics of five representative TCP schemes, namely, TCP New Reno, Vegas, Veno, Westwood, and BIC, in WiMAX (and WLANs) networks, under the conditions of correlated wireless errors, asymmetric end-to-end capabilities, and link congestion. The target is to evaluate how the above conditions would affect the TCP congestion control and suggest the best schemes to be employed in WiMAX networks.